Effects of Direct Intervention on Identification, Blending, and Segmenting of Phonemes - Hansen, Elayne (My University, 2015)
The purpose of this study was to determine if PA skills in typically developing children can be increased by providing intervention on identification, blending, and segmenting of phonemes. It was also to investigate other variables that may affect the development of PA skills.
Color poster with text and graphs.
Keywords: Child literacy; Phonemes; Posters